Давньоугорські та «салтоїдні» знахідки у Лівобережному Придніпровському терасовому лісостепу Полтавщини - Кулатова, І.М.; Супруненко, О.Б. (Археологія і давня історія України, 2011)
Публікація характеризує рештки зруйнованих давньоугорських і так званих «салтоїдних» поховань, виявлених вздовж лівого берега
Дніпра в межах південно-західної Полтавщини, датованих ІХ – рубежем ІХ–Х ст. В публикации приводится характеристика комплексов разрушенных древнеугорских и некоторых «салтоидных» погребений,
обнаруженных по левому берегу Днепра на юго-западе Полтавской области, информация о находках гончарной керамики ІХ в. It is made a survey of complexes of ruined Old-
Magyar and Saltoid graves, which were found
throughout the left bank area of Dnieper in the
South-Western part of the Poltava Region. It is
also given the information on finds of ceramics,
dated back to the ninth and the turn from the ninth to the tenth centuries.